Pemberdayaan Masyarakat Dalam Pembuatan Pakan Lele Menggunakan Pedicle Kerang Lentera Dan Pendampingan Evaluasi Manajemen Usaha Budidaya Ikan - Retno, Ria; Tambunan, Lois; Sirait, Debora (Journal Of Human And Education (JAHE), 2024)
Aras Village is a village in Air Putih District, Batu Bara Regency, North Sumatra Province. The people who live in the Aras Village area are farmers, fish cultivators and traders. The partner's problem is that they have never received training in making independent feed and evaluating their cultivation business. So far, fish farmers in Aras Village still rely on factory-made feed, causing the price of the feed product to be very high, reaching 70% of the total production costs and they cannot evaluate their business. The aim of community empowerment activities is to assist fish farmers in managing and increasing fish farmers' income in managing catfish cultivation. The priority aim of community service carried out by lecturers is to improve the economy. The stages of the implementation method used are outreach and training to the community on how to make good and healthy fish food. Socialization, training and assistance to the catfish farming community on how to evaluate catfish cultivation businesses by calculating income, expenses, BEP, B/C ratio and NPV (overcoming management problems). Evaluation of program implementation is carried out every time an activity is carried out, such as socialization, training and mentoring. Socialization and training on making independent feed and evaluating fisheries businesses is going well in Aras Village, Air Putih District, Batu Bara Regency. The program evaluation results show that as many as 80% of cultivator groups can know how to make feed independently and evaluate their efforts.